2007
DOI: 10.1007/s00125-007-0797-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in glycaemic control and risk of coronary artery disease in type 1 diabetes mellitus: findings from the Pittsburgh Epidemiology of Diabetes Complications Study (EDC)

Abstract: Aims/hypothesis To complete a comparative analysis of studies that have examined the relationship between glycaemia and cardiovascular disease (CVD)/coronary artery disease (CAD) and perform a prospective analysis of the effect of change in glycosylated Hb level on CAD risk in the Pittsburgh Epidemiology of Diabetes Complications Study (EDC) of childhood-onset type 1 diabetes mellitus (n=469) over 16 years of two yearly follow-up.Methods Measured values for HbA 1 and HbA 1c from the EDC were converted to the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 32 publications
3
71
2
Order By: Relevance
“…A recent comparative analysis on CVD and coronary artery disease risk in type 1 diabetes, based on findings from the Pittsburgh Epidemiology of Diabetes Complications Study, suggested that glycemia may have a stronger effect on coronary artery disease in patients without albuminuria than in those with albuminuria (24). Our results were different because glycemia had a prominent effect on CVD mortality in type 1 diabetic subjects with proteinuria.…”
Section: -Total and Cvd Mortality During 18 Years Of Follow-up In Typcontrasting
confidence: 86%
“…A recent comparative analysis on CVD and coronary artery disease risk in type 1 diabetes, based on findings from the Pittsburgh Epidemiology of Diabetes Complications Study, suggested that glycemia may have a stronger effect on coronary artery disease in patients without albuminuria than in those with albuminuria (24). Our results were different because glycemia had a prominent effect on CVD mortality in type 1 diabetic subjects with proteinuria.…”
Section: -Total and Cvd Mortality During 18 Years Of Follow-up In Typcontrasting
confidence: 86%
“…Intensive insulin therapy is important in avoiding diabetesrelated microvascular and macrovascular complications [1], but may also have a role in preserving residual beta cell function [2]. Levels of C-peptide are now being increasingly recognised as a primary endpoint in intervention trials in patients with newly diagnosed type 1 diabetes [3].…”
Section: Introductionmentioning
confidence: 99%
“…4 Finally, the importance of glycaemic control for the type 1 DM patients has become even more relevant due to recent demonstration that more intensive glycaemic control is associated to the lower CVD development in these patients. 31,32 Besides that, there is an intrinsic relation of glycaemic control to pressure values, verified through the assessment of patients placed, for intensive treatment, in the Diabetes Control and Complication Trial. 33 It was demonstrated that the better glycaemic control of type 1 DM patients is capable of preventing HPT.…”
Section: Discussionmentioning
confidence: 99%